This is philosophy an introduction - Hales, Steven D. (Hoboken, NJ, USA Wiley Blackwell, 2021)
"The present book takes a third path. Although it includes commentary on the great historical philosophers and tries to show contemporary relevance, the book introduces students to philosophy topically. While there are references to Buddhism, the Vedas, Islam, and so on, the issues addressed are the bread-and-butter mainstream subjects in broadly analytic Western philosophy. Any student who successfully completes a course based on this book will have a solid grounding in wide variety of topics in different subdisciplines, as well as the pros and cons of different theoretical ways to address those topics. A student who masters the content of this book is well-placed to move on as a philosophy major in the vast majority of philosophy departments. The problems of philosophy are deeply interconnected, and there is no natural or obvious starting point from which to begin. Indeed, plausible arguments might be given for starting with almost any of the central problems in the field. You might think that we should surely start with epistemology; until we understand what knowledge is and settle the matter of whether and how we can gain any knowledge at all, how can we possibly determine whether we can have knowledge of God, or our moral duties, or the nature of the mind? Clearly epistemology is the most fundamental philosophical project. Wait-how can we be sure that knowledge is valuable to have? Or that we ought to care about gaining truth and avoiding error? We'd better start with axiology and sort out duty, obligation, and responsibility first. Normativity and ethics must be foundational. Of course, how can we determine what our epistemic responsibilities are if we don't antecedently know whether we are free to believe one thing rather than another, or if we are truly at liberty to make choices? Let's begin with the issue of free will and figure that out first. If we're not free, that torpedoes a lot of other philosophical agendas. Yet if we don't know what kinds of beings we are, how can we ever determine whether we are free? Maybe personal identity should be the first stop on the road. And so on"--Provided by publisher.
1.1. Is Morality Just Acting on Principles? -- 1.2. Divine Command Theory (Is Morality Just What God Tells Me to Do?) -- 1.3. Egoism (Is Morality Just My Own Personal Code?) -- 1.4. Moral Relativism (Is Morality Just How Society Says We Should Act?) -- 2.1. Utilitarianism (Is Morality Doing What I Can to Make This the Best World Possible?) -- 2.2. Deontology, or Kantianism (Is There an Absolute Moral Law?) -- 2.3. Objections -- 2.4. Virtue Ethics (Is Morality all about Having a Virtuous Character?) -- 2.5. Objections -- 3.1. The Attributes of God -- 3.2. Why There is a God -- 3.3. Why There is No God -- 3.4. Atheist Responses to the Free Will Defense -- 4.1. Against Free Will, Part 1: Divine Foreknowledge -- 4.2. Against Free Will, Part 2: A Regress of Reasons for Acting -- 4.3. Against Free Will, Part 3: Determinism and the Dilemma Argument -- 4.4. The Incompatibilist Argument -- 4.5. The Dilemma Argument Against Free Will -- 4.6. Free Will and Moral Responsibility -- 4.7. Agent Causation -- 4.8. Compatibilism -- 4.9. The Feeling of Freedom -- 5.1. Preliminary Positions -- 5.2. The Soul Criterion -- 5.3. Objections -- 5.4. The Physicalist Criterion -- 5.5. The Psychological Criterion -- 5.6. The Bundle Theory -- 6.1. Substance Dualism -- 6.2. Behaviorism -- 6.3. Mind-brain Identity Theory -- 6.4. Functionalism -- 7.1. The Value of Truth -- 7.2. The Value of Evidence -- 7.3. The Sources of Evidence -- 7.4. The Nature of Knowledge -- 7.5. The Skeptic's Challenge -- 8.1. State of Nature -- 8.2. Anarchy -- 8.3. Contractarianism -- 8.4. Leviathan and the Philosopher Kings -- 8.5. The Minimal State -- 8.6. The Liberal State.
Includes bibliographical references and index.
Keywords: Philosophy -- Introductions